(untitled) - Desurvire, Emmanuel (Hoboken, N.J., 2004)
The book provides a comprehensive approach to telecom accessible to a broad audience. Each chapter concludes with a summary and exercises with solutions in some cases. Advanced equations requiring math background to appear only in the Appendix, and references are limited to books and review papers deemed accessible to the book’s intended broad audience.
Keywords: Signal processing,Computer networks,Xử lý tín hiệu,Mạng máy tính